Aunt Jane's Nieces in the Red Cross - Baum, L. Frank (Lyman Frank), 1856-1919; Hall, N. P. (Salt Lake City, UT : Project Gutenberg, 2005)
"Aunt Jane's Nieces in the Red Cross" by L. Frank Baum is a young adult novel published in 1915. When war erupts in Europe, three American girls sacrifice comfort to serve as nurses on a converted hospital ship. Confronting military bureaucracies and battlefield horrors, they treat wounded soldiers while grappling with the brutal realities of World War I. Their idealistic mission faces mounting challenges, including a disfigured surgeon haunted by fear, tragedy on the front lines, and questions about their place in a foreign conflict. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Aunt_Jane%27s_Nieces_in_the_Red_Cross
Release date is 2005-08-21
E-text prepared by Afra Ullah, Emmy, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: War stories; Family -- Juvenile fiction; Red Cross and Red Crescent -- Juvenile fiction; Nurses -- Juvenile fiction; World War, 1914-1918 -- Medical care -- Juvenile fiction